The impact of postgraduate education in transition to practice programmes on new graduate nurses' knowledge and skills: A pre- post survey design. (July 2021) - Doughty, Lesley; Sinnema, Claire; McKillop, Ann; Dixon, Robyn
Abstract: Background: Research indicates that nurses perceive postgraduate education to have a positive effect on their knowledge and practice. Many jurisdictions offer/require new graduate nurses to undertake postgraduate coursework however the consequences of this are not clear. Objectives: This research aims to determine the impact of completing a postgraduate course in clinical assessment on the capabilities of new graduate nurses. Design: A two group pre/post design with a naturally occurring intervention employing an online questionnaire was used to gather data. Settings: Two metropolitan hospitals in New Zealand delivering new graduate programmes, one inclusive of a postgraduate course and the other not. Participants: Eighty five nurses completed the questionnaire on commencement of the programme and fifty-two on completion of the programme. Methods: An online questionnaire was administered to two new graduate cohorts, on commencement and completion of their new graduate programme. Results: Results showed significant pre/post increases for four out of five factors for those who had completed a postgraduate course compared to only one significant increase for those who had not. In addition, when comparing the scores of the two groups there was no significant differences between groups on the pre-measures. However, on post measures there were significant differences with the postgraduate group scoring higher on three of the five subscales: Knowledge for Practice, Explaining Practice and Applied Diagnostic Reasoning. Conclusion: It is the author's belief that this is the first study that has attempted to quantify new graduate nurses' perceptions of their educational experience in their first year of practice and suggests that the inclusion of the postgraduate course enhanced knowledge for practice and diagnostic reasoning skills. Highlights: There is value to completing postgraduate education in the first year of practice. A targeted assessment course enhances knowledge, skill and diagnostic reasoning. New graduate nurses benefit from completing postgraduate education.